Comparative Study of Constant Height Mode and Constant Detection Mode in Atomic Force Microscopy (AFM) Imaging. - Lau, Sai Yee (2016)
Atomic Force Microscopy (AFM) is a kind of Scanning Probe Microscopes (SPM) which is designed to measure local properties of materials, such as height, area, friction and magnetism, using a probe that operates at high resolution. AFM demonstrates scanning resolution on the order of fractions of a nanometer and thus it is widely used in Nano technology. The development of AFM is important as it helps to overcome the basic weakness of optical microscope, which is limited by optical diffraction limit in scanning, and also the weakness of Scanning Tunnel Microscopy (STM), which can only produce images on conducting and non-conducting surface. Increasing use of AFM has been found in diverse field of technology, such as physical and biological sciences and it was predicted that this trend will continue. In view of this, the purpose of this project is to develop a functional software prototype AFM scanning mechanism through LABVIEW platform and features will be further discussed in the report. The work here focuses on the comparative study of Constant Height mode and Constant Deflection mode in AFM imaging. Basic framework of system was constructed in the early phase so that further integration and improvement can be achieved progressively. In the last phase of prototyping development, there will be a software prototype which works as AFM scanning mechanism, in LABVIEW. Involvement of NI ELVIS board is mainly for future integration with real-case AFM machine.